Drug Combinations for Visceral Leishmaniasis - Olliaro, P. L. (2012)
PURPOSE OF REVIEW: Several attempts have been made to combine drugs for treating visceral leishmaniasis, but only recently have effective drugs become available and combinations been tested systematically. RECENT FINDINGS: Sequential treatments with liposomal amphotericin B followed by miltefosine or paromomycin (as short as 7 days), as well as the concomitant administration of miltefosine and paromomycin (for 10 days) are very effective in India (>95%). Sodium stibogluconate plus paromomycin for 17 days is more than 90% effective in East Africa. The shortened combination regimens are cost-effective in India. No combination has been tested so far in Brazil, Nepal and Bangladesh, although studies may be expected in the near future. No cost-effectiveness analysis has been done as yet outside India. SUMMARY: There is evidence of high efficacy and benefits with sequential and co-administration treatments in India. More studies are needed in other endemic areas. Introducing combinations and scaling up their use will be challenging. Experience acquired with malaria may be useful. Proper monitoring of use and effects (efficacy and safety) will be required. Currently there are no options for fixed-dose combination treatments for leishmaniasis.